The link between active aging and retirement age - PAŞNICU, Mihai Robert (Annals of Spiru Haret University. Economic Series, 2014)
The paper aims to shed light on the policies and consequences of the current retirement age in Romania. The retirement age has been repeatedly incremented in Romania in the last couple of years in order to try to compensate for the fact that the country has a low general employment rate, only 30% of the population, while having 20% of the total population aged 65+. By using an econometric model we will first prove the existence of an optimal retirement age that might vary for each and every one of us, after which we will explore different possibilities of exploiting this information in order to improve the current retirement programs. Mainly, we will look at the possible solution of eliminating the mandatory retirement age in certain work sectors through a comparison analysis.